MOFs-Based Nitric Oxide Therapy for Tendon Regeneration - Chen, Jun; Sheng, Dandan; Ying, Ting; Zhao, Haojun; Zhang, Jian; Li, Yunxia; Xu, He; Chen, Shiyi (Nano-Micro Letters, 2020)
Tendon regeneration is still a great challenge due to its avascular structure and low self-renewal capability. The nitric oxide (NO) therapy emerges as a promising treatment for inducing the regeneration of injured tendon by angiogenesis. Here, in this study, a system that NO-loaded metal–organic frameworks (MOFs) encapsulated in polycaprolactone (PCL)/gelatin (Gel) aligned coaxial scaffolds (NMPGA) is designed and prepared for tendon repair. In this system, NO is able to be released in vitro at a slow and stable average speed of 1.67 nM h−1 as long as 15 d without a burst release stage in the initial 48 h. Furthermore, NMPGA can not only improve the tubular formation capability of endothelial cells in vitro but also obviously increase the blood perfusion near the injured tendon in vivo, leading to accelerating the maturity of collagen and recovery of biomechanical strength of the regenerated tendon tissue. As a NO-loaded MOFs therapeutic system, NMPGA can promote tendon regeneration in a shorter healing period with better biomechanical properties in comparison with control group by angiogenesis. Therefore, this study not only provides a promising scaffold for tendon regeneration, but also paves a new way to develop a NO-based therapy for biomedical application in the future. Highlights: 1 A system that NO-loaded metal–organic frameworks encapsulated in PCL/Gel aligned coaxial scaffold is successfully constructed. 2 The system enables to release NO slowly (1.67 nM h−1) and stably in a long period (15 d) without a burst release in the initial 48 h. 3 The scaffold can promote the regeneration of the injured tendon with maturer collagen fibers and better mechanical properties by angiogenesis.